Le nous latino-américain et son émancipation: altérités, imagination et mémoire - Marcelo Velarde Cañazares (Centre de Recherches sur les Mondes Américains, 2008)
The need for the assertion of oneself and the need for a “second independence” (emancipation) are still important challenges for the Latin-American notion of identity. Following the concept of otherness, this text shows certain paradoxes related to the dialectical links between identity and independence, and also to the imaginary of mythical or utopian dimensions in the collective memory of the Latin-American peoples. The question drives us to emphasize that the alternative thought tends to fight the myth of inferiority which affects their self-esteem, by means of an active rescue of identity functions, both utopias and myths. By rescuing this imaginary dimension would contribute to the reinforcement of an alternative collective memory, linked to the actions towards emancipation.